2020
DOI: 10.4018/ijtd.20201001.oa
|View full text |Cite
|
Sign up to set email alerts
|

Approaches and Trends of Automatic Bangla Text Summarization

Abstract: As long as the internet user is increasing, online electronic content is growing proportionally irrespective of languages. A lot of research works on English text summarization have come to light to deal with this gigantic body of online text. Unfortunately, a few works have been accomplished for Bangla though a huge number of people are involved with this language. This article has tried to explore the trend of research work on Bangla text summarization. Fourteen approaches have been briefly expounded here by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
(88 reference statements)
0
5
0
Order By: Relevance
“…The RMSE and correlation scores indicate the degree to which the two mentioned social networks coincide, with a very low RMSE score and a significant correlation (p-value) suggesting that the constructed social network is very close to the ideal ground truth network. This has implications as a novel method for a text summarization procedure and as an alternative to the contemporary techniques [56][57][58]. This is particularly significant for the text summarization of fiction, which depends greatly on elements such as characters and social relations [59].…”
Section: Discussionmentioning
confidence: 99%
“…The RMSE and correlation scores indicate the degree to which the two mentioned social networks coincide, with a very low RMSE score and a significant correlation (p-value) suggesting that the constructed social network is very close to the ideal ground truth network. This has implications as a novel method for a text summarization procedure and as an alternative to the contemporary techniques [56][57][58]. This is particularly significant for the text summarization of fiction, which depends greatly on elements such as characters and social relations [59].…”
Section: Discussionmentioning
confidence: 99%
“…Bangla text data preprocessing's most common challenges are character-set dependence, corpus dependence, applica-tion dependence, writing system dependence, tokenizing of punctuations, tokenizing of space-delimiters, preprocessing of Bangla grammatically wrong words, preprocessing of ambiguous words, preprocessing of erroneous words, preprocessing multi-label Bangla data. Moreover, the automatic computerized services for Bangla text preprocessing and relevant research works are hardly available for facilitating researches on Bangla language text data [81], [191].…”
Section: Current Challenges and Future Trends In Bnlp A Challenges In...mentioning
confidence: 99%
“…We found that Yeasmin et al [1] have described the different techniques regarding abstractive approaches. Then as we decided to focus on abstractive text summarization approaches on the Bengali language context, we covered Haque et al [2] where 14 approaches of Bengali text summarization regarding both extractive and abstractive approaches are described. In 2004, Islam et al [3] first introduced Bengali extractive summarization based on document indexing and keyword-based information retrieval.…”
Section: Related Workmentioning
confidence: 99%